PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN PELECEHAN DI BAWAH UMUR - Zainudin Hasan; Intan Annisa; Aulia Rizky Hafizha; Anis Nurhalizah (Jurnal Hukum dan Sosial Politik, 2023)
A connection or contact in which a kid is exploited as a sexual object for the gratification of an adult's sexual wants, such as a parent, sibling, or stranger, constitutes sexual violence against children. Children must be safeguarded from violence and prejudice while living, growing, developing, and participating in society to the fullest extent feasible, in accordance with human dignity and values. This study's focus is, thus, on ending child abuse in the Indonesian city of Bandar Lampung. The Bandar Lampung Police Women and Children Protection Unit's (PPA Unit) preventative efforts include community outreach and counseling on child protection, school-based preventative socialization and legal education on sexual violence crimes, and training and education on sexual and reproductive health rights as a required course, CCTV facilities and emergency management buttons, violence prevention teams specifically for sexual violence and standard operating procedures for prevention and competency tests and exploration activities against sexual violence and collaboration with agencies -Agency related to child protection.